The Effect of Doing Qualitative Research on Novice Researchers - Scott, Ann (European Journal for Qualitative Research in Psychotherapy, 2008)
This study investigates the effect of doing qualitative research on novice researchers. The heuristic approach as outlined by Moustakas 1990 was applied to reports given by six novice researchers on their experience of qualitative research, either in a heuristic or phenomenological framework. Analysis of these reports supported earlier work in showing that a common feature of this experience is enmeshment of the investigator with the research topic, with resulting consequences in their personal lives. This enmeshment is described, taking one report as exemplar and using additional material from other reports in support. The study concludes with some personal reflections including an allegorical story expressing the experience under investigation as understood by the researcher.